2020
DOI: 10.1186/s13756-020-00798-3
|View full text |Cite
|
Sign up to set email alerts
|

A seven-year surveillance study of the epidemiology, antifungal susceptibility, risk factors and mortality of candidaemia among paediatric and adult inpatients in a tertiary teaching hospital in China

Abstract: Background: There are no current national estimates of the candidaemia burden in China, and epidemiological candidaemia data from the underdeveloped region of China are lacking. Methods: A 7-year retrospective study was carried out to analyse the prevalence, species distribution, antifungal susceptibility, risk factors and inpatient mortality of candidaemia among paediatric and adult patients in a regional tertiary teaching hospital in China. Results: During the seven-year study period, a total of 201 inpatien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
2
16
1
1
Order By: Relevance
“…Similarly, studies from the USA have also reported higher incidence values, with a total of ≥7 cases per 100,000 inhabitants [ 23 , 24 , 54 , 57 ]. Epidemiological studies from China (26 cases per 100,000 hospital admissions compared to 90 cases per 100,000 patients in the USA) have also reported incidence values which are comparable to the data from Kuwait and European countries [ 23 , 24 , 58 , 59 , 60 ]. One study from Thailand, however, reported a higher incidence rate of 13.3 per 100,000 individuals [ 61 ].…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, studies from the USA have also reported higher incidence values, with a total of ≥7 cases per 100,000 inhabitants [ 23 , 24 , 54 , 57 ]. Epidemiological studies from China (26 cases per 100,000 hospital admissions compared to 90 cases per 100,000 patients in the USA) have also reported incidence values which are comparable to the data from Kuwait and European countries [ 23 , 24 , 58 , 59 , 60 ]. One study from Thailand, however, reported a higher incidence rate of 13.3 per 100,000 individuals [ 61 ].…”
Section: Discussionsupporting
confidence: 61%
“…infections are associated with considerable all-cause mortality that varies from nearly 20% to more than 60% in different patient populations from various geographic regions/countries and is higher among patients in the ICU. 4,5,10,11,[17][18][19] Epidemiological studies carried out in the last two decades showed that more than 90% of Candida spp. infections are caused by only five species/species-complexes which include C albicans, C tropicalis, C parapsilosis, C glabrata and C krusei.…”
Section: Introductionmentioning
confidence: 99%
“…causing invasive infections at some geographical locations/healthcare facilities. 18,[23][24][25] Furthermore, infections caused by uncommon or emerging Candida spp. as well as infections with drugresistant strains have increased considerably in select patient populations in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown reduced susceptibility to fluconazole or voriconazole among C. glabrata isolates ( Song et al, 2020 ; Zeng et al, 2020 , 2021 ), such as the large survey of Candida isolates from the Asia-Pacific region ( Tan et al, 2016 ). A study examining 77 hospitals in China (across seven administrative regions) over a period of 3 years has shown an overall fluconazole resistance rate of 10.2% (3.1–11.4%) and a decrease in voriconazole susceptibility in C. glabrata ( Xiao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%